Pendampingan Pelatihan Manasik Haji dalam Meningkatkan Pemahaman Siswa tentang Ajaran Islam di SDN 01 Prajegan. - Mar'ahtus Solihah; Asfahani Asfahani; Fuad Fitriawan (Social Science Academic, 2025)
The Hajj pilgrimage is the fifth pillar of Islam, but only some have the opportunity to perform it due to time and cost constraints. However, as Muslims, we must know the pillars and procedures. This community service aims to determine the Hajj manasik training in improving students' understanding of Islamic teachings at SDN 1 Prajegan. The method used in this community service is PAR (Participation Action Research), which involves the community and conducting in-depth interviews with eight students and two religious teachers. The results of this community service show that the Hajj manasik provides profound benefits for students, makes students understand more about the Hajj simulation, and is very effective in helping students understand abstract religious concepts, such as the pillars of Islam and prayer procedures. Students find remembering and practicing Islamic teachings easier after participating in the Hajj manasik activities. Through the assistance of the Hajj Manasik training, students' understanding of Islamic teachings in elementary schools can be improved.